2018
DOI: 10.1152/ajpcell.00336.2017
|View full text |Cite
|
Sign up to set email alerts
|

Olfactomedin 4 contributes to hydrogen peroxide-induced NADPH oxidase activation and apoptosis in mouse neutrophils

Abstract: Neutrophils increase production of reactive oxygen species, including superoxide, hydrogen peroxide (HO), and hydroxyl radical, to destroy invading microorganisms under pathological conditions. Conversely, oxidative stress conditions, such as the presence of HO, induce neutrophil apoptosis, which helps to remove neutrophils after inflammation. However, the detailed molecular mechanisms that are involved in the latter process have not been elucidated. In this study, we investigated the potential role of olfacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Previous studies evaluating the role of OLFM4 in murine neutrophils have been under the assumption that all neutrophils express OLFM4 protein. 21,22,34,35 Furthermore, these studies were done on the C57Bl6 background, which we show here to only express OLFM4 in 6-8% of neutrophils. This perhaps suggests that some of the observed phenotype differences, such as differences in superoxide production and increased killing of bacteria, may be due to secreted OLFM4 rather than the intrinsically expressed OLFM4, because differences reported would be attributable to only 6-8% of neutrophils.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Previous studies evaluating the role of OLFM4 in murine neutrophils have been under the assumption that all neutrophils express OLFM4 protein. 21,22,34,35 Furthermore, these studies were done on the C57Bl6 background, which we show here to only express OLFM4 in 6-8% of neutrophils. This perhaps suggests that some of the observed phenotype differences, such as differences in superoxide production and increased killing of bacteria, may be due to secreted OLFM4 rather than the intrinsically expressed OLFM4, because differences reported would be attributable to only 6-8% of neutrophils.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies evaluating the role of OLFM4 in murine neutrophils have been under the assumption that all neutrophils express OLFM4 protein (21, 22, 34, 35). Furthermore, these studies were done on the C57Bl6 background, which we show here to only express OLFM4 in 6–8% of neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in mice have shown OLFM4 to potentially play a role in down-regulation of the innate immune response in murine Helicobacter pylori infection by inhibiting cathepsin G (13)(14)(15). Another study showed that OLFM4 may be involved in superoxide production to augment neutrophil apoptosis (26). However, these studies were carried out assuming that all neutrophils expressed OLFM4, whereas the finding that only a subset of murine neutrophils express OLFM4 was only recently published (12).…”
Section: Discussionmentioning
confidence: 99%
“…OLFM4 gene expression in the whole blood was upregulated in septic patients with acute respiratory distress syndrome [ 53 ]. OLFM4 contributed to H 2 O 2 -induced NADPH oxidase activation and cellular apoptosis in mouse neutrophils [ 54 ]. Conversely, the contradictory results of OLFM4 on inflammation have been reported in several studies.…”
Section: Discussionmentioning
confidence: 99%